(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The word "job satisfaction" refers to people’s overall attitudes toward their jobs. It refers to an individual’s satisfaction and well-being in relation to their performance at work. It may be an excellent measure of a company’s productivity. Organizations should prioritize the job satisfaction of their employees. Employees that are content may be more optimistic, imaginative, and driven to succeed. Employee expectations and a collaborator’s behavior toward supervisors and coworkers are two aspects that may come into play.